2022
DOI: 10.1002/ep.13857
|View full text |Cite
|
Sign up to set email alerts
|

Potential for optimization of energy consumption and costs in saffron production in central Iran through data envelopment analysis and multi‐objective genetic algorithm

Abstract: Technical management of agricultural units plays an important role in increasing the yield, energy efficiency, and decreasing the production costs. Based on that, the present study aimed to evaluate and optimize the technical and economic efficiency in Saffron farms in the 2019-20 cropping season in Iran. Required data were collected from 70 Saffron farms through interviews and questionnaires and were analyzed and compared using two optimization methods including data envelopment analysis (DEA), and multi-obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…On the other hand, Khorramdel et al [19] observed a higher proportion of renewable energy compared to non-renewable energy but a higher share of direct energy compared to non-direct energy. Saeidi et al [23] observed more direct energy but a higher proportion of non-renewable energy compared to renewable energy. In summary, the comparison reveals consistent patterns in the dominance of renewable and indirect energy sources, but variations exist in the proportion and share of direct, indirect, renewable, and non-renewable energy among different studies.…”
Section: Energy Forms and Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Khorramdel et al [19] observed a higher proportion of renewable energy compared to non-renewable energy but a higher share of direct energy compared to non-direct energy. Saeidi et al [23] observed more direct energy but a higher proportion of non-renewable energy compared to renewable energy. In summary, the comparison reveals consistent patterns in the dominance of renewable and indirect energy sources, but variations exist in the proportion and share of direct, indirect, renewable, and non-renewable energy among different studies.…”
Section: Energy Forms and Typesmentioning
confidence: 99%
“…In the context of saffron cultivation in Iran [13], the literature reports energy use efficiency, specific energy, and energy productivity values of 1.12, 13.35 MJ kg −1 , and 0.0749 kg MJ −1 , respectively, based on the combined metrics of stigma and by-products. Based on saffron stigma only, the values reported were 0.0044, 22.05 MJ kg −1 , and 0.0003 kg MJ −1 in the east of Iran [16]; 0.24 (0.0004), 51,235.15 MJ kg −1 , and 0.000019 kg MJ −1 in the northeast of Iran [12]; 0.035, 5590.72 MJ kg −1 , and 0.00018 kg MJ −1 in the northeast of Iran [22]; and 0.002, 8794.85 MJ kg −1 , and 0.00011 kg MJ −1 in the center of Iran [23].…”
Section: Energy Balance and Performance Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers frequently employ micro-level data garnered through meticulous surveys to conduct efficiency assessments within localized geographical scopes. Noteworthy examples include studies that have used data from70 Saffron farms in Iran (Saeidi et al, 2022), rice farms in Korea (Nguyen et al, 2012), greenhouse tomato cultivation in Turkey (Turkten and Ceyhan, 2023), irrigated chickpea production in Iran and shrimp aquaculture in Vietnam (Trang et al, 2023). Second, a subset of researchers have studied this topic from the macroscopic perspective, using datasets spanning nine East Asian nations (Le et al, 2019) or focusing on a provincial scale within China (Guo et al, 2022;Zhang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saffron planting is considered a strategic and vital component of the national economy of Iran due to its unique position in job creation in the agricultural sector and the creation of significant foreign exchange income for this country. Some of the particular advantages of saffron are low irrigation, high product durability, exploitation for 5-7 years in one planting period, ease of transportation, productive employment, and significant currency enhancement, which has led to the development of its cultivated area in Iran, especially in areas without agricultural potential (Saeidi et al, 2022). The product's compatibility has made Iran the largest producer of saffron in the world, producing 430 tons of saffron in 2019, more than 90% of global production and 3.5% of global market share (Statista, 2020).…”
Section: Introductionmentioning
confidence: 99%